2015
DOI: 10.1111/spc3.12161
|View full text |Cite
|
Sign up to set email alerts
|

Got Pain? Racial Bias in Perceptions of Pain

Abstract: In the days of slavery, White people assumed that Black people felt less pain than did White people. This belief was used to justify slavery; it was also used to justify the inhumane treatment of Black men and women in medical research. Today, White Americans continue to believe that Black people feel less pain than do White people although this belief has changed from its historical, explicitly racist form. Racial attitudes do not moderate the bias, suggesting that racial bias in perceptions of others' pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 47 publications
5
46
1
1
Order By: Relevance
“…This opposite bias perhaps reflects real-world differences, as previous work has shown that black patients tend to report greater pain than do white patients (7,24,42). This opposite bias could also reflect participants' attempt to compensate for known racial disparities (see ref.…”
Section: Studymentioning
confidence: 95%
See 4 more Smart Citations
“…This opposite bias perhaps reflects real-world differences, as previous work has shown that black patients tend to report greater pain than do white patients (7,24,42). This opposite bias could also reflect participants' attempt to compensate for known racial disparities (see ref.…”
Section: Studymentioning
confidence: 95%
“…In the United States, these beliefs were championed by scientists, physicians, and slave owners alike to justify slavery and the inhumane treatment of black men and women in medical research (20)(21)(22)(23)(24)(25). In the 19th century, prominent physicians sought to establish the "physical peculiarities" of blacks that could "serve to distinguish him from the white man" (23).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations